Experimental investigation on mechanical behavior of sandwich structures using Digital Image Correlation (DIC) (Fracture and Structural Integrity, 2025)
The aim of this work is to investigate the mechanical behavior of sandwich structures when subjected to edgewise and flatwise compression loadings, using 2D Digital Image Correlation (DIC). These structures are made of Glass Fiber Reinforced Polymer (GFRP) skins with polyurethane foam (PU) core. Initially, the mechanical characterization of each component within the sandwich structure is exanimated. Subsequently, flatwise and edgewise compression tests are conducted on the sandwich panels, in accordance with ASTM C365 and ASTM C364 standards, respectively. Different geometries are studied by testing various lengths of sandwich structures exposed to edgewise compression loads. The DIC technique is applied to analyze and comprehend the deformation and failure mechanisms of GFRP skins and sandwich structures. The results of the present study indicate that the flatwise compression test revealed condensation and densification of PU foam, accompanied by microcracks in GFRP skin. On the other hand, the edgewise compression test on sandwich structures with an equal length-to-width ratio identified several distinct failure modes, including skin-core debonding, shear sliding damage of the skin, and localized buckling. This localized buckling was initially observed in the mid-section of the specimens, followed by skin cracking on both sides, which then propagated across the width of the samples. For other geometric configurations of the sandwich structures, the Euler general buckling mode was observed. The results show that the length of samples has a significant effect on the collapse modes of sandwich structures under edgewise compression.
Keywords: Sandwich structure; PU; GFRP; 2D DIC; behavior